2021
DOI: 10.17557/tjfc.943458
|View full text |Cite
|
Sign up to set email alerts
|

VARIATIONS AMONG MAIZE (Zea Mays L.) HYBRIDS IN RESPONSE TO HEAT STRESS: HYBRIDS SELECTION CRITERIA

Abstract: High ambient temperature is one of the most alarming climatic factors in challenging the productivity and sustainability of crops worldwide. An effective way to cope this problem is the development of climate smart, heat resilient maize hybrids through evaluating the cultivated germplasm. The main objective of current study was to evaluate local and multinational maize hybrids for their performance under optimal and heat stress conditions and to devise a selection criterion for the identification of heat toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This result is partly consistent with a previous report (Amegbor et al, 2022). Yousaf et al (2021) showed the negative association between starch and fat content.…”
Section: Biplot Analysissupporting
confidence: 94%
“…This result is partly consistent with a previous report (Amegbor et al, 2022). Yousaf et al (2021) showed the negative association between starch and fat content.…”
Section: Biplot Analysissupporting
confidence: 94%
“…Correlation coefficient analysis was adopted to investigate the relationship between different parameters of cotton genotypes under heat stress conditions. Correlation analysis is one of the most basic statistical approaches utilized by researchers to explore the association between different plant traits under different circumstances including heat stress Yousaf et al 2021a;Yousaf et al, 2021b;Riaz et al;Rahman et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For this, different statistical approaches could be used but multivariate analysis provides the best possible solution for the selection of genotypes. It is considered one of the best methods to evaluate crop genotypes worldwide under stressed and non-stressed conditions (Munir et al, 2020, Yousaf et al, 2021a, Rahmanet al, 2022. Therefore, multivariate modelbased approaches i.e., Principal component and cluster analysis were applied to screen cotton genotypes for their tolerance against high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal temperature for maize growth and development varies from stage to stage and during the light and dark hours. During daylight, it grows best between 25 and 33 °C, whereas during dark hours, 17–23 °C is required . However, mean temperature throughout the growing season is 20–22 °C.…”
Section: How Do Drought and Heat Stress Affect Maize Crop?mentioning
confidence: 99%
“…During daylight, it grows best between 25 and 33 °C, whereas during dark hours, 17−23 °C is required. 35 However, mean temperature throughout the growing season is 20−22 °C. The optimum temperature for germination is slightly on the higher side, i.e., 25−28 °C.…”
Section: How Does Heat Stress Affect Maize Crop?mentioning
confidence: 99%